GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG ANTIBIOTIK DI APOTEK KOTA MATARAM - Syamsul Rahmat; Lalu Jupriadi; Dedent Eka Bimmahariyanto (Akademi Farmasi Yarsi Pontianak, 2021)
Antibiotics are a type of drug that is used to treat or prevent infectious diseases caused by bacteria. Community self-medication using antibiotiks is an inappropriate step that should concern us all. Increasing antibiotik resistance in several developing countries threatens developments in the health and food sector. This study aims to determine the level of public knowledge in a pharmacy in Mataram about antibiotics. This research is a non-experimental study with a descriptive observational cross sectional design. The research was conducted by interviewing pharmacy visitors who came to buy drugs. This research was conducted for one month from June to July 2020 with 106 respondents. Respondents' knowledge was categorized into three levels. Based on the assessment that has been carried out from the results of the questionnaire, it was found that most of the respondents had a low level of knowledge (59%) and sufficient level of knowledge (33%), while 8% had a good level of antibiotic knowledge. The low level of knowledge is probably due to the use of antibiotics in the community in an inappropriate manner, which has become the culture of the community. Further research needs to be carried out using more pharmacies and with a larger sample with different socio-cultural and environmental conditions